The Power of Isolation - Podjed, Dan; Peternel, Lana (Traditiones, 2024)
This article investigates isolation as a complex physical and symbolic phenomenon. The studies presented in the article and in this special issue explore how isolation impacts identities, social cohesion, and community life – especially in times of ongoing and interconnected crises. The authors examine the multifaceted nature of isolation that informs daily practices, emotional wellbeing, and community bonds, offering insights into the challenges and resilience seen in isolated communities.